IMPLEMENTASI MODEL GAME BASED LEARNING BERBANTUAN WORDWALL DAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH SISWA - Arassati; Rahman Haryadi; Dwi Oktaviana (STKIP Subang, 2026)
This study aims to compare the effectiveness of Game Based Learning (GBL) model assisted by wordwall with Problem Based Learning (PBL) on the mathematical problem-solving ability of class X students of SMA Negeri 1 Sungai Raya on the material of arithmetic sequences and series. The research method used Quasi Experimental Design with Nonequivalent Control Group Design. The sample was selected through purposive sampling, namely class X8 as the experimental class (31 students) who implemented GBL assisted by wordwall and class X6 as the control class (31 students) who implemented PBL. The research instrument used was a problem-solving ability test on the material of arithmetic sequences and series. Data were analyzed using paired sample t-test and independent t-test. The results showed that both models were able to improve students' mathematical problem-solving ability. The experimental class increased from 58.60 to 84.94 with N-Gain 0.64 (medium category), while the control class increased from 59.03 to 71.93 with N-Gain 0.31 (medium category). The independent t-test shows tcount = 4.3255 > ttable = 2.0003 (α = 5%), so the mathematical problem-solving ability of students taught using GBL assisted by wordwall is better than PBL. Digital games create interesting and challenging learning, encouraging active student involvement.